2011
DOI: 10.1371/journal.pone.0024883
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Expression Profile of MicroRNAs in Porcine Pituitary

Abstract: MicroRNAs (miRNAs) are an abundant class of small RNAs that regulate expressions of most genes. miRNAs play important roles in the pituitary, the “master” endocrine organ.However, we still don't know which role miRNAs play in the development of pituitary tissue or how much they contribute to the pituitary function. By applying a combination of microarray analysis and Solexa sequencing, we detected a total of 450 miRNAs in the porcine pituitary. Verification with RT-PCR showed a high degree of confidence for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 44 publications
1
29
0
2
Order By: Relevance
“…Although transcriptional regulation of gonadotropin subunits has been well studied (10, 12, 19 -22) as described above, the post-transcriptional mechanisms that regulate gonadotropin subunits are unknown (23,24). Of the three pituitary glycoprotein hormone subunit-encoding genes (Cga, Lhb, and Fshb), Fshb gene is unique in its organization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although transcriptional regulation of gonadotropin subunits has been well studied (10, 12, 19 -22) as described above, the post-transcriptional mechanisms that regulate gonadotropin subunits are unknown (23,24). Of the three pituitary glycoprotein hormone subunit-encoding genes (Cga, Lhb, and Fshb), Fshb gene is unique in its organization.…”
mentioning
confidence: 99%
“…These include mRNA expression, turnover, stability, and translational control (36 -41). Expression profiling studies have identified several miRNAs differentially regulated in whole pituitary (23,24), various pituitary cell lineages (42), human pituitary tumors (43)(44)(45), and in an immortalized gonadotrope cell line in response to GnRH treatment (46 -48). In addition, specific miRNAs regulating a repressor that selectively regulates LH levels in the female have also been identified (49).…”
mentioning
confidence: 99%
“…Elsősorban állatmodellek vizsgálata alapján tudjuk, hogy a miRNS-ek fontosak az agyalapi mirigy fiziológiás működésében, és hiányuk agyalapimirigy-rendellenességhez vezet [16][17][18][19][20], ám konkrét szerepükről kevés adat áll rendelkezésre. Egér esetében a miRNS-ek érésé-hez szükséges Dicer enzim specifikus kiütése a gonadotrop sejtekben csökkentette a gonadotropinok szintjét, és megváltozott reprodukciós funkciókat, csökkent fertilitást okozott hím egereknél [21].…”
Section: Mirns-expressziós Eltérések Az Agyalapimirigy-daganatokbanunclassified
“…(Table 3) Although most research has hitherto been dedicated to miRNA's roles in meat quality, emerging research has evaluated miRNA in other solid tissues in pigs, including, but not limited to, reproduction. Many miRNAs are enriched in reproductive tissues [4,15,17,44] ( Table 3). Others may play a role in differentiating neurons in brain development [3,13,[70][71][72][73].…”
Section: Origins and Mechanisms Of Mirnasmentioning
confidence: 99%
“…The common research strategy on miRNA may include three aims: (i) characterization of miRNAs (including identification of novel miRNAs), (ii) determination of target genes, and (iii) illumination of function of miRNAs and target genes. These strategies have been widely used to describe the miRNAome in various pig tissues, such as muscle [9][10][11][12], brain [13], fat [14], embryo [3], pituitary [15], intestine [16], ovary [17] and testes [4].…”
Section: Introductionmentioning
confidence: 99%